Jeremiah's poems of lament - Baumgartner, Walter, 1887-1970. (Sheffield, England : Almond Press, 1988)
"A translation by David E. Orton of Die Klagegedichte des Jeremia, the seminal work by Walter Baumgartner examining the so-called 'confessions' of Jeremiah."--Bloomsbury Publishing.
Translation of: Die Klagegedichte des Jeremia.
Includes bibliographical references and index.
Also issued in print.
Electronic reproduction.
Keywords: Bible. -- Criticism, interpretation, etc